PENINGKATAN HASIL BELAJAR IPA MATERI KALOR DAN PERPINDAHANNYA DENGAN PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DENGAN METODE WORD SQUARE - Jainuri Jainuri (MEDIA DIDAKTIKA, 2022)
This study aims to determine the increase in science learning outcomes in terms of heat and transfer by using the Numbered Heard Together cooperative learning model with the Word Square method in class V SD Negeri 4 Lamongrejo, Ngimbang District, Lamongan Regency, in the 2021/2022 academic year. Research instruments include lesson plans, teacher observation sheets, and evaluation tests. The results showed that the NHT type cooperative learning model with evaluation using the word square method could improve the learning outcomes of fifth grade students at SD Negeri 4 Lamongrejo, Ngimbang District, Lamongan Regency in 2022. The increase in students who complete learning from Pre-Cycle to Cycle I was 54.84% and Cycle I to Cycle II was 25.81%. This can be seen in the acquisition of completeness of student learning outcomes in the Pre-Cycle which has an average of 56.61, Cycle I has an average of 74.03 and Cycle II has an average of 79.83 Students have achieved a classical KKM of 100%.